A supply chain management guide to business continuity - Kildow, Betty A. (American Management Association, 2011)
A well-monitored supply chain is any business' key to productivity and profit. But each link in that chain is its own entity, subject to its own ups, downs, and business realities. This book identifies the different phases of business continuity program development and maintenance